Medial Temporal Lobe Activation in Learning - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Regional cerebral blood flow was examined by PET recordings during multiple-trial learning in healthy volunteers tested at Guy's and St Thomas's Hospitals and the MRC Cyclotron Unit, Hammersmith Hospital, London.